Neonatal Antibiotic Treatment Is Associated With an Altered Circulating Immune Marker Profile at 1 Year of Age - Oosterloo, Berthe C.; van't Land, Belinda; de Jager, Wilco; Rutten, Nicole B.; Klöpping, Margot; Garssen, Johan; Vlieger, Arine M.; van Elburg, Ruurd M. (Frontiers in Immunology, 2020)
Background Neonatal antibiotics disturb the developing gut microbiome and are therefore thought to influence the developing immune system, but exact mechanisms and health consequences in later life still need to be elucidated. Therefore, we investigated whether neonatal antibiotics influence inflammatory markers at one year of age. In addition, we determined whether health problems during the first year of life, e.g. allergic disorders (eczema and wheezing) or infantile colics, were associated with changes in the circulating immune marker profile at one year. Methods In a subgroup (N=149) of the INCA-study, a prospective birth-cohort study, a blood sample was drawn from term born infants at one year of age and analyzed for 84 immune related markers using Luminex. Associations of antibiotic treatment, eczema, wheezing and infantile colics with immune marker concentrations were investigated using a linear regression model. The trial is registered as NCT02536560. Results The use of broad-spectrum antibiotics in the first week of life, was significantly associated with different levels of inflammatory markers including sVCAM-1, sCD14, sCD19, sCD27, IL-1RII, sVEGF-R1 and HSP70 at one year of age. Eczema was associated with decreased concentrations of IFNα, IFNγ, TSLP, CXCL9 and CXCL13, but increased concentrations of CCL18 and Galectin-3. Wheezing, independent of antibiotic treatment, was positively associated to TNF-R2 and resistin. Infantile colics were positively associated to IL-31, LIGHT, YKL-40, CXCL13, sPD1, IL1RI, sIL-7Ra, Gal-1, Gal-9 and S100A8 at one year of age, independent of early life antibiotic treatment. Conclusion In this explorative study, we identified that neonatal antibiotics induce certain immunological alterations at one year of age and that, independent of the antibiotic treatment, infantile colics were associated with altered gut associated markers. These findings support the importance of the first host microbe interaction in early life immune development.